Pengasuhan Orang Tua pada Anak dengan Stunting di Kecamatan Siantar Utara, Kota Pematangsiantar - Hanna Letare Winroriauli Sinaga; Berlianti Berlianti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This study was motivated by the high number of stunted children found in stunting locations, namely in Kelurahan Kahean and Sigulang-gulang, Kecamatan Siantar Utara, Kota Pematangsiantar. This study also found indications of inadequate parenting patterns in terms of nutrition and child health care. This condition is a serious concern because stunting not only affects children's physical growth but also influences their cognitive development and future quality of life. To understand this phenomenon in depth, this study used a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observations, literature studies, and documentation, involving six main informants. The results of the study revealed that 4 of the 6 parents with stunted children practiced inadequate parenting, particularly neglectful parenting, which was the most dominant parenting style. This neglectful parenting style was characterized by a lack of adequate supervision and attention to providing nutritious food and health care for children. Parents who apply this parenting style tend to consistently ignore their children's nutritional and health needs, thereby increasing the risk of stunting. In addition, some parents also apply a permissive parenting style, which is characterized by allowing children to freely choose food without clear boundaries or rules. As a result, children often consume unhealthy foods and have irregular eating schedules. In addition to parenting factors, limited socioeconomic conditions also exacerbate the risk of stunting. Parents' low level of knowledge about balanced nutrition and child health care further increases the likelihood of children experiencing stunting. This shows that economic and educational factors are major obstacles in efforts to prevent stunting in the Kecamatan Siantar Utara.